Study of creep of nickel in external magnetic field - Karas, V.I.; Sokolenko, V.I.; Karasyova, E.V.; Mats, A.V.; Vlasenko, A.M. (Вопросы атомной науки и техники, 2015)
The creep of nickel in external magnetic field was studied. It was shown that at turning on and turning off of the magnetic field a drastic weakening of nickel takes place. The magnitude of weakening depends on the magnetic field change rate. It is shown that the sole reason for explanation of the observed effect of material plasticity increasing is the dynamics of nonequilibrium electron-phonon subsystem caused by eddy electric field influence. Досліджено повзучість нікелю в зовнішньому магнітному полі. Показано, що при ввімкненні та вимк-ненні магнітного поля відбувається різке знеміцнення нікелю. Величина знеміцнення залежить від швидкості зміни магнітного поля. Показано, що єдиною причиною, що пояснює спостережений ефект знеміцнення матеріалу, є вплив вихрового (індукційного) електричного поля на динаміку нерівноважної електрон-фононної підсистеми. Исследована ползучесть никеля в изменяющемся внешнем магнитном поле. Показано, что при включении и выключении магнитного поля происходит резкое разупрочнение никеля. Величина разупрочнения зависит от скорости изменения магнитного поля. Показано, что единственной причиной, объясняющей наблюдаемый эффект разупрочнения материала, является влияние вихревого (индукционного) электрического поля на динамику неравновесной электрон-фононной подсистемы.